UTILIZATION OF LIQUID ORGANIC FERTILIZER (LOF) FROM GOAT MANURE ON Lemna sp. BIOMASS IN THE MAINTENANCE MEDIA FOR SNAKEHEAD FISH (Channa striata) - Ayu Mita Jami Yanti; Saberina Hasibuan; Rodhi Firmansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Snakehead fish (Channa striata) culture produces waste in the form of leftover feed that can reduce water quality. One approach to improving water quality is the use of the aquatic plant Lemna sp. for phytoremediation. However, Lemna sp. growth requires sufficient nutrients; therefore, liquid organic fertilizer (LOF) derived from goat manure was applied. This study aimed to determine the optimal dose of goat manure LOF for Lemna sp. biomass production in snakehead fish culture water. The study was conducted from September to October 2025 at the Integrated Laboratory of Marine Sciences, Universitas Riau. A completely randomized design with five treatments and three replicates was used. Treatments were P0 (control), P1 (0,5 mL/L), P2 (1,0 mL/L), P3 (1,5 mL/L), and P4 (2,0 mL/L). The results showed that goat manure LOF significantly affected Lemna sp. biomass (P < 0.05). The best treatment was P4, producing the highest biomass (362.58 g/m²) and specific growth rate (6.56%). Application of goat manure LOF also supported snakehead fish growth, resulting in a final mean weight of 3.20 g, mean length of 3.88 cm, daily weight gain of 2.60 g/day, and survival rate of 98%. In total organic matter ranged from 16.43–55.72 mg/L, nitrate 0.1813–10.0229 mg/L, phosphate 0.6991–5.1416 mg/L, CO₂ 5–18 mg/L, DO 4.10–5.21 mg/L, pH 6.2–7.4, and temperature 27.1–28.9°C. These findings indicate that goat manure LOF at 2.0 mL/L effectively increases Lemna sp. biomass, promotes phytoremediation, and improves snakehead fish growth and survival.